2014
DOI: 10.1159/000363659
|View full text |Cite
|
Sign up to set email alerts
|

Early versus Delayed Surgery for Acute Cholecystitis as an Applied Treatment Strategy When Assessed in a Population-Based Cohort

Abstract: Background: The aims of this study were to describe the surgical management of acute cholecystitis (AC) in a well-defined population-based patient cohort, in particular adherence to and outcome of the early open/laparoscopic cholecystectomy (EC/ELC) strategy. Methods: The medical records of all patients residing in Stockholm County who were treated for AC during 2003 and 2008 were reviewed according to a standardized protocol. Results: In 2003, 799 patients were admitted 850 times for AC, and the respective fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…However, the implementation of this evidence-based practice is a real obstacle for many hospitals. A recent study in Sweden showed no major changes in the management of acute cholecystitis between 2003 and 2008 despite evidence favouring early surgery [104]. One reason for failing to implement early LC for acute cholecystitis is the lack of access to emergency operating theatre time and a culture that acute cholecystitis is not a surgical emergency.…”
Section: Discussionmentioning
confidence: 99%
“…However, the implementation of this evidence-based practice is a real obstacle for many hospitals. A recent study in Sweden showed no major changes in the management of acute cholecystitis between 2003 and 2008 despite evidence favouring early surgery [104]. One reason for failing to implement early LC for acute cholecystitis is the lack of access to emergency operating theatre time and a culture that acute cholecystitis is not a surgical emergency.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with moderate cholecystitis (defined by severe local inflammation), or patients with increased operative risk due to significant comorbidities (even with mild local disease), are treated by I.V antibiotics (further referred as conservative treatment). Moreover, technical and organizational difficulties hamper the implementation of early cholecystectomy even in surgically fit patients [6][7][8][9]. Thus, many patients are not operated at the same admission, but are treated conservatively.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 89 full‐text articles were assessed for eligibility, and 26 articles were included in the study. Details of relevant excluded studies are shown in Table S1 (supporting information). Of the 26 included articles, 24 were eventually used in the meta‐analysis, because four described the same two studies.…”
Section: Resultsmentioning
confidence: 99%